Clinical and genetic characterization of Bardet–Biedl syndrome in Tunisia: defining a strategy for molecular diagnosis. (5th April 2013) - M'hamdi, O.; Redin, C.; Stoetzel, C.; Ouertani, I.; Chaabouni, M.; Maazoul, F.; M'rad, R.; Mandel, J.L.; Dollfus, H.; Muller, J.; Chaabouni, H.
<x xml:space="preserve">Abstract</x> Bardet–Biedl syndrome (BBS, OMIM 209900) is a rare genetic disorder characterized by obesity, retinitis pigmentosa, post axial polydactyly, cognitive impairment, renal anomalies and hypogonadism. The aim of this study is to provide a comprehensive clinical and molecular analysis of a cohort of 11 Tunisian BBS consanguineous families in order to give insight into clinical and genetic spectrum and the genotype–phenotype correlations. Molecular analysis using combined sequence capture and high‐throughput sequencing of 30 ciliopathies genes revealed 11 mutations in 11 studied families. Five mutations were novel and six were previously described. Novel mutations included c.1110G>A and c.39delA (p.G13fs*41) in BBS1, c.115+5G>A in BBS2, c.1272+1G>A in BBS6, c.1181_1182insGCATTTATACC in BBS10 (p.S396Lfs*6). Described mutations included c.436C>T (p.R146*) and c.1473+4A>G in BBS1, c.565C> (p.R189*) in BBS2, deletion of exons 4–6 in BBS4, c.149T>G (p.L50R) in BBS5, and c.459+1G>A in BBS8; most frequent mutations were described in BBS1 (4/11, 37%) and BBS2 (2/11, 18%) genes. No phenotype–genotype correlation was evidenced. This data expands the mutations profile of BBS genes in Tunisia and suggests a divergence of the genetic spectrum comparing Tunisian and other populations.